The Multidimensional Prognostic Index as a Measure of Frailty in Elderly Patients with Head and Neck Cancer - Bakas AT (Dove Medical Press, 2021)
Ajay T Bakas,1 Aniel Sewnaik,1 Jaclyn van Straaten,2 Robert J Baatenburg de Jong,1 Francesco US Mattace-Raso,2 Harmke A Polinder-Bos2 1Department of Otorhinolaryngology, Erasmus MC University Cancer Institute, Rotterdam, the Netherlands; 2Division of Geriatric Medicine, Department of Internal Medicine, Erasmus MC University Medical Center, Rotterdam, the NetherlandsCorrespondence: Ajay T BakasDepartment of Otorhinolaryngology, Erasmus MC University Cancer, Institute, Rotterdam, the NetherlandsTel +31-10-7040704Email a.bakas@erasmusmc.nlPurpose: The multidimensional prognostic index (MPI) is a prognostic model derived from the comprehensive geriatric assessment (CGA) which can predict 1-year mortality risk in elderly individuals. We hypothesized that the MPI also reflects the degree of frailty and thus will correlate with established measures of frailty. Therefore, the aim of this study is to explore whether the MPI-score is a measure of frailty in older head and neck cancer patients and is associated with several physical functioning measurements.Patients and Methods: From November 2019 to July 2020, a prospective cohort study enrolled patients with head and neck cancer aged ≥ 70 years, and patients < 70 years with an abnormal G8 score. The MPI-score ranged from 0 to 1 and was categorized in MPI-stage 1 (≤ 0.33, non-frail); MPI-stage 2 (0.34– 0.66, mildly frail), and MPI-stage 3 (≥ 0.67, severe frail). Pearson’s correlation coefficient and multivariable linear regression were used to study the association between MPI-score and the physical functioning measurements handgrip strength, gait speed, and the timed up and go test (TUGT).Results: A total of 163 patients were included. One hundred four (63.8%) patients were categorized as non-frail according MPI-stage 1, and 59 (36.2%) patients as mildly or severe frail (n=55 MPI-stage 2; n=4 MPI-stage 3, respectively). A higher MPI-score was significantly associated with lower hand grip strength (B − 0.49 [95% CI − 0.71; − 0.28] p< 0.001), lower gait speed (B − 0.41 [95% CI − 0.55; − 0.25] p< 0.001), and a slower TUGT (B 0.53 [95% CI 0.66; 0.85] p< 0.001).Conclusion: Almost one-third of the included patients with head and neck cancer was mild or severe frail. A higher MPI-score, indicating higher degree of frailty, was associated with worse physical performance by lower handgrip strength, gait speed, and a slower TUGT. Thus, the MPI reflects the degree of frailty.Keywords: comprehensive geriatric assessment, sarcopenia, head and neck cancer, multidimensional prognostic index, elderly